Isolation, Screening, and Characterization of Carbonatogenic Bacteria From Bukit Bulan Lime Soil as Alternative Biocement Agents for Self-Healing Concrete Cracks - Kurniawan, Hafiz Muchti; Yulianto, Didik; Bestnissa, Nadya; Satria, Darma; Pratomo, Soni (Department of Biology, Faculty of Science and Technology, Syarif Hidayatullah State Islami, 2026)
Eight carbonatogenic bacterial isolates have been successfully isolated from the limestone soils of Bukit Bulan, Jambi Province, Indonesia. This research aims to obtain superior bacteria as biocement agents that can help the self-healing process of concrete cracks. The eight carbonatogenic bacteria are isolates coded BB1, BB2, BB3, BB4, BB5, BB6, BB7, and BB8. Qualitative screening revealed that all isolates were capable of forming calcium carbonate (CaCO₃) precipitation in the test medium. Quantitative tests revealed that all isolates were capable of producing precipitation of calcium carbonate (CaCO₃). CaCO₃ crystals produced by carbonatogenic bacteria exhibit properties of both calcite and vaterite phases, which can potentially enhance the strength of concrete structures. Seventy-five % of the isolates are gram-positive, and 25% are gram-negative. All isolates can produce the enzyme cytochrome oxidase C, which enhances the natural self-healing ability of bacteria in repairing concrete. All isolates can decompose urea, suggesting that they may contribute to the formation of CaCO₃ minerals. The motility test revealed that 50% of carbonatogenic bacteria are motile, which can enhance the efficiency in self-healing concrete. When applied to concrete mixtures, it is known that the carbonatogenic bacteria BB1, BB2, BB3, and BB4 can aid in repairing concrete cracks. The BB3 isolate can close concrete cracks faster than other isolates, indicating that it has the potential to be further developed as a biocement agent.